PROBLEMS OF ADAPTATION OF STUDENTS-PRACTICAL PSYCHOLOGISTS TO STUDYING IN THE HIGHER EDUCATIONAL INSTITUTION - Литвинчук H. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2019)
The article deals with the problems of the process of adaptation of freshmen students to study at a higher educational institution. It is noted that the issue of adaptation of a young person to the new conditions of life is extremely important, since the initial stage of study is the most difficult period in the life of students. And from how the adaptation stage will be completed depends the success of the student’s educational activity, the attitude to the future profession, his becoming a future professional. The author analyzes scientific literature and theoretical understanding of the problem of adaptation. The number of scientific papers on this topic indicates an active study of this problem and its relevance. In scientific sources, it is noted that the problem of adapting students to the conditions of the new environment is one of the essential general theoretical problems that are studied on the psycho-physiological, individual psychological, socio-psychological levels. The article presents the theoretical analysis of adaptation as a process and adaptability of students to study at a higher education institution. The difficulties faced by the first-year students, entering into a new stage of life, are analyzed. The reasons that determine the difficulties of the adaptation period are considered. As a result of this analysis, it is concluded that student adaptation is a complex, multilateral and dynamic process that depends on many factors. The article raises issues of factors influencing the adaptation of freshmen students and determine the indicators of adaptability. Among such factors are factors of professional, biological, social, psychological adaptation, and each and every kind has external and internal attribute. The author argues that the psychological factors that have a significant impact on the success of adaptation are insufficiently studied and require further research. The results of the survey of freshmen students of the specialization "Practical Psychology" of the National Aviation University are presented in the article, such results fully confirm the theoretical calculations concerning the problems of the adaptation process of yesterday’s school students with regards to study at a higher education institution